2022
DOI: 10.1021/acs.biochem.2c00513
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Selectivity in CalA Lipase: Beyond Tunnel Engineering

Abstract: Engineering studies of Candida (Pseudozyma) antarctica lipase A (CalA) have demonstrated the potential of this enzyme in the selective hydrolysis of fatty acid esters of different chain lengths. CalA has been shown to bind substrates preferentially through an acyl-chain binding tunnel accessed via the hydrolytic active site; it has also been shown that selectivity for substrates of longer or shorter chain length can be tuned, for instance by modulating steric hindrance within the tunnel. Here we demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The hydrophobic pore could provide an additional layer of substrate discrimination for mammalian lipases beyond the previously identified lid peptide and hydrophobic binding pocket. In that regard, the pore might utilize a similar specificity mechanism to the tunnel seen in C. rugosa lipase and other homologs (53, 54). This could provide an explanation for why LPL preferentially hydrolyzes the sn-1 and sn-3 position on triglycerides, as the sn-2 acyl chain interacts in a separate hydrophobic pocket facilitating enhanced substrate recognition of the sn-1 or sn-3 position by the hydrophobic pore.…”
Section: Discussionmentioning
confidence: 95%
“…The hydrophobic pore could provide an additional layer of substrate discrimination for mammalian lipases beyond the previously identified lid peptide and hydrophobic binding pocket. In that regard, the pore might utilize a similar specificity mechanism to the tunnel seen in C. rugosa lipase and other homologs (53, 54). This could provide an explanation for why LPL preferentially hydrolyzes the sn-1 and sn-3 position on triglycerides, as the sn-2 acyl chain interacts in a separate hydrophobic pocket facilitating enhanced substrate recognition of the sn-1 or sn-3 position by the hydrophobic pore.…”
Section: Discussionmentioning
confidence: 95%
“…The results align with earlier studies that demonstrated the role of dynamics for substrate binding, catalysis and as a valuable tool for enzyme engineering together with other computational and experimental approaches. 99,136,137,197–203…”
Section: Resultsmentioning
confidence: 99%
“…The results align with earlier studies that demonstrated the role of dynamics for substrate binding, catalysis and as a valuable tool for enzyme engineering together with other computational and experimental approaches. 99,136,137,[197][198][199][200][201][202][203] How the substrate Asp103 hFX binding mode A inuence the catalytic reaction of dioxygen activation? The high spin quintet state of Fe(III)-O-Oc − is reported to be the most favorable spin state for dioxygen activation in non-heme dioxygenases.…”
Section: Resultsmentioning
confidence: 99%
“…This process leads to decreased fatty acid utilization in the final product. 26 However, there is a paucity of research on substrate selectivity between n-3 PUFAs and saturated fatty acids with the same chain length, especially regarding the important n-3 PUFA, DHA. The primary hindrance is the limited research on precise structural differences among substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, ongoing studies aim to enhance the lipase selectivity for long-chain fatty acids. Alejaldre et al investigated mutants carrying substitutions within the substrate tunnel and distal regions, yielding the Candida antarctica lipase A (CalA) variant LS_66 (A32T/L172M/R262H/L274W/G432D) with selectivity for long-chain palmitic acid . However, there is a paucity of research on substrate selectivity between n-3 PUFAs and saturated fatty acids with the same chain length, especially regarding the important n-3 PUFA, DHA.…”
Section: Introductionmentioning
confidence: 99%